2009
DOI: 10.1016/j.engfailanal.2008.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Mould steels repaired by laser welding

Abstract: Laser-deposit welding, by using Nd-YAG, is a mould repairing process, which has the advantages relatively to the traditional methods of achieving a less change of the metal composition around the repaired zone and permitting a very accurate deposition of a small volume of the filler material in the area chosen at the work-piece surface. This paper presents a fatigue study in specimens of two base materials used in mould production (AISI H13 and P20). Filler material as well as welding parameters were analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 8 publications
0
26
0
1
Order By: Relevance
“…In a previous work [1,2], the authors observed (see Figs. 3 and 4) that welded specimens, tested at R = 0, present a significant lower fatigue resistance than the correspondent non-welded specimens tested for the same stress ratio.…”
Section: Experimental Residual Stressesmentioning
confidence: 93%
See 2 more Smart Citations
“…In a previous work [1,2], the authors observed (see Figs. 3 and 4) that welded specimens, tested at R = 0, present a significant lower fatigue resistance than the correspondent non-welded specimens tested for the same stress ratio.…”
Section: Experimental Residual Stressesmentioning
confidence: 93%
“…In a previous work [1,2], the authors observed that welded specimens, tested at R = 0.4, presented a similar fatigue resistance to the correspondent non-welded specimens tested for the same stress ratio and also very close to the curve obtained with welded specimens for R = 0. Residual stresses are probably the main factor affecting this fatigue behaviour.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Para aquéllos materiales que son sensibles al agrietamiento y cambios en la composición debidos a la formación de fases frágiles, la formación de carburos primarios y secundarios M 23 C 6 y M 7 C 6 . Debido a las condiciones del proceso, las cuales combinan una relativamente baja temperatura de flama con un bajo tiempo de exposición [4]. Este método emplea una alta presión de un combustible (propileno, acetileno, propano o gases de hidrógeno) para producir temperaturas del gas superior a los 3,029 ºK y para generar una supersónica o hipersónica velocidad del gas, de aproximadamente 2,000 m/s, más de cinco veces la velocidad del sonido [5].…”
Section: Introductionunclassified
“…Composite repair of thick section was carried out (Jones and Chiu 1999). Repairing of part by laser technology was carried out (Wang et al 2002;Borrego et al 2009). Non-destructive inspection techniques to detect cracks were employed (Diamanti et al 2005).…”
Section: Literature Review In Repair Technologymentioning
confidence: 99%